Molecular Ecology Comparison of Blue Leg Hermit Crab (Calcinus elegans) based on Spatial Factor in South Coast of Java Island - Muliawati Handayani; Sutrisno Anggoro; Ita Widowati; Imai Hideyuki (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
The study was conducted to determine the genetic diversity of Calcinus elegans based on sequences of the COI mitochondrial DNA. Successfully 54 samples of Garut; 43 of Yogyakarta and 47 of Banyuwangi populations were amplified by PCR using universal primers LCO 1490 and HCO 2198 successfully amplified COI gene in 625 bp, with an overall haplotype totaled 64 at 111 polymorphic sites. All population showed high genetic diversity within population interpreted by the value of gene diversity (H): Garut is 0.9266 ± 0.0251; Yogyakarta is 0.9668 ± 0.0156 and Banyuwangi is 0.9288 ± 0.0257 and the value of nucleotide diversity (π): Garut is 0.007155 ± 0.003972; Yogyakarta is 0.007966 ± 0.004387 and Banyuwangi is 0.00723 ± 0.004021. Gene diversity and nucleotide diversity did not differ significantly between populations. While genetic diversity among populations interpreted from haplotypes similarity or shared haplotype. Number of shared haplotypes among three populations is 12 haplotypes with 90 samples included. Banyuwangi population showed smallest intensity interaction with other populations indicated by the smallest value of haplotypes; polymorphic sites; hetorozigosity and distribution of larvae are influenced by spatial factor. However, three populations come from one ancestors and part of a large population. Thus the current and other environmental factors in South Coast of Java Island are effected on the genetic diversity among populations of C. elegans with a correlation coefficient is r = 0.98 (genetic diversity with current) and r = >0.90 (genetic diversity with temperature, salinity, pH, depth and distance).   Key words: Calcinus elegans, genetic diversity, COI, mitochondrial DNA, haplotype